Overexpression of cytoplasmic TcSIR2RP1 and mitochondrial TcSIR2RP3 impacts on Trypanosoma cruzi growth and cell invasion. - Carla Ritagliati; Victoria L Alonso; Romina Manarin; Pamela Cribb; Esteban C Serra (Public Library of Science (PLoS), 2015)
Trypanosoma cruzi is a protozoan pathogen responsible for Chagas disease. Current therapies are inadequate because of their severe host toxicity and numerous side effects. The identification of new biotargets is essential for the development of more efficient therapeutic alternatives. Inhibition of sirtuins from Trypanosoma brucei and Leishmania ssp. showed promising results, indicating that these enzymes may be considered as targets for drug discovery in parasite infection. Here, we report the first characterization of the two sirtuins present in T. cruzi.Dm28c epimastigotes that inducibly overexpress TcSIR2RP1 and TcSIR2RP3 were constructed and used to determine their localizations and functions. These transfected lines were tested regarding their acetylation levels, proliferation and metacyclogenesis rate, viability when treated with sirtuin inhibitors and in vitro infectivity.TcSIR2RP1 and TcSIR2RP3 are cytosolic and mitochondrial proteins respectively. Our data suggest that sirtuin activity is important for the proliferation of T. cruzi replicative forms, for the host cell-parasite interplay, and for differentiation among life-cycle stages; but each one performs different roles in most of these processes. Our results increase the knowledge on the localization and function of these enzymes, and the overexpressing T. cruzi strains we obtained can be useful tools for experimental screening of trypanosomatid sirtuin inhibitors.